Perbandingan Sustainability Report antara Bank Syariah Indonesia (BSI) dan Bank Mandiri Berdasarkan Global Reporting Initiative (GRI) Tahun 2022-2023 - Nafakhatussahariyyah, Nafakhatussahariyyah; Utami, Cahyaning Budi (Universitas Islam Lamongan, 2024)
This research aims to determine the comparison of sustainability reports between Bank Syariah Indonesia (BSI) and Bank Mandiri based on global reporting initiative (GRI) 2022-2023 or to what extent are these two banks committed to implementing GRI standards in presenting transparent and accountable sustainability information? This research uses comparative qualitative descriptive research. By collecting data using secondary data obtained from sustainability reports published by BSI and Bank Mandiri 2022-2023 which can be accessed on their respective websites. This research shows that both banks have a strong commitment to economic, environmental and social performance, although with different approaches and scales. Bank Mandiri has a higher operating scale and numbers, while BSI shows consistent growth and focuses on social and environmental aspects in line with sharia financial principles. This research provides insights into best practices and areas of improvement in sustainability reporting in the banking industry.